2020
DOI: 10.1101/2020.04.13.039446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exogenous L-lactate promotes astrocyte plasticity but is not sufficient for enhancing striatal synaptogenesis or motor behavior in mice

Abstract: L-lactate is an energetic and signaling molecule that is key to the metabolic and neuroplastic connection between astrocytes and neurons and may be involved in exercise-induced neuroplasticity. This study sought to explore the role of L-lactate in astrocyte reactivity and neuroplasticity. Using in vitro cultures of primary astrocytes, we show L-lactate increased expression of plasticity-related genes, including neurotrophic factors, Bdnf, Gdnf, Cntf and the immediate early gene cFos. L-lactate's promotion of n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Lactate is known to be a signalling molecule for neuronal plasticity in cultured mouse primary neurons and in vivo in the mouse sensory-motor cortex [ 82 ]. Recently, Lundquist et al [ 83 ] observed an increase in the expression of BDNF in primary astrocytes treated with l-lactate in-vitro. They also demonstrated that l-lactate administration to healthy mice led to increased astrocyte morphological complexity, as well as astrocyte-specific neurotrophic expression within the striatum, a critical component of the motor and reward systems [ 83 ].…”
Section: Hormones and Metabolites Of The Muscle–brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate is known to be a signalling molecule for neuronal plasticity in cultured mouse primary neurons and in vivo in the mouse sensory-motor cortex [ 82 ]. Recently, Lundquist et al [ 83 ] observed an increase in the expression of BDNF in primary astrocytes treated with l-lactate in-vitro. They also demonstrated that l-lactate administration to healthy mice led to increased astrocyte morphological complexity, as well as astrocyte-specific neurotrophic expression within the striatum, a critical component of the motor and reward systems [ 83 ].…”
Section: Hormones and Metabolites Of The Muscle–brain Axismentioning
confidence: 99%
“…Recently, Lundquist et al [ 83 ] observed an increase in the expression of BDNF in primary astrocytes treated with l-lactate in-vitro. They also demonstrated that l-lactate administration to healthy mice led to increased astrocyte morphological complexity, as well as astrocyte-specific neurotrophic expression within the striatum, a critical component of the motor and reward systems [ 83 ]. Interestingly, increases in peripheral blood lactate levels at rest in humans have been associated with an increase in circulating BDNF [ 84 ].…”
Section: Hormones and Metabolites Of The Muscle–brain Axismentioning
confidence: 99%